La técnica del pase y las acciones tácticas ofensivas de mini basquet en la Unidad Educativa Miguel Suarez Seminario - Cortez Mina, Bélgica Catalina (2017)
This includes the descriptive analysis of mini-basketball, the planning of sports training, the design of the methodological proposal and the application of the results obtained during the teaching-learning process: mainly our project is based on improving the techniques of passing in their offensive tactical actions , related to the training and initiation of the practice of this sport in the aforementioned context. In this project we worked mainly in the development of basic fundamentals and physical qualities, as well as in the control of anthropometric measurements and the resistance test applied before and after the whole training process to boys and girls that were part of the investigation after this of showing with comparative pictures in the progress of the children improving their physical capacities and therefore helping poor development and body growth, and also show that in this canton there are good human elements to encourage sporting activity and especially the mini-basketball.